Clinical and EEG Features of Idiopathic Focal Epilepsies in Childhood - Caraballo, Roberto H.; Darra, Francesca; Bernardina, Bernardo Dalla; Fejerman, Natalio (Journal of Pediatric Epilepsy, 2016)
The International League Against Epilepsy (ILAE) report lists three well-defined syndromes of idiopathic focal epilepsies in childhood: benign childhood epilepsy with centrotemporal spikes (BCECTS), Panayiotopoulos syndrome (PS), and idiopathic childhood occipital epilepsy of Gastaut (ICOE-G). The concept of idiopathic and benign focal epilepsies in childhood is relevant as the term implies absence of structural brain lesions and genetic predisposition in the presence of age-dependent seizures. BCECTS is the most frequent of the benign focal epilepsies in childhood accounting for 15 to 25% of epilepsy syndromes in children below 15 years of age. It is also the most frequent epilepsy syndrome occurring at school age. The prevalence of PS was around 13% in children aged 3 to 6 years with one or more nonfebrile seizures, and 6% in the age group of 1 to 15 years. These figures may be higher if children who are currently considered to have an atypical clinical presentation are included in the syndrome. PS is the most common specific cause of nonfebrile status epilepticus in childhood. ICOE “Gastaut type” is a rare manifestation of a focal idiopathic epilepsy that has an age-related onset and is often age limited. The seizures of ICOE Gastaut type are always of occipital-lobe onset and primarily manifest with visual seizures, which are the most typical and usually the first ictal symptom, but other types of seizures may be associated. ICOE “Gastaut type” is a rare condition with a probable prevalence of 0.2 to 0.9% of all epilepsies, and accounting for 2 to 7% of benign childhood focal seizures.The recognition of these age-dependent epileptic syndromes is crucial for the adequate management of the children and their family.
Keywords: childhood; epilepsy; focal; centrotemporal spikes; occipital spikes; idiopathic